1967
DOI: 10.1136/adc.42.225.525
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's syndrome associated with an islet-cell tumour of the pancreas in a boy aged 2 years.

Abstract: We present this case because, so far as we can discover, no similar one has yet been reported in a child.Case History This boy was born in June 1963. He presented at the out-patient clinic in September of 1965 at the age of 2 years and 3 months, on account of sudden excessive weight gain. He had been healthy and free of symptoms until 6 weeks before, when he had suddenly developed a ravenous appetite ('he will eat two of every meal I offer him'). He had become very fat and his face had become very red. His wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Doppman et al found only one adult (out of 53 cases) with islet cell tumor producing ACTH that was due to a benign adenoma 9 . The children reported all succumbed to their disease 1 " 9 , except the patient of Burkinshaw et al 6 who was tumor free at 1 year of follow-up. In their series of 12 patients, Amikara et al reported median survival of 2.5 years, with all patients showing evidence of recurrent disease 12 .…”
Section: Discussionmentioning
confidence: 95%
“…Doppman et al found only one adult (out of 53 cases) with islet cell tumor producing ACTH that was due to a benign adenoma 9 . The children reported all succumbed to their disease 1 " 9 , except the patient of Burkinshaw et al 6 who was tumor free at 1 year of follow-up. In their series of 12 patients, Amikara et al reported median survival of 2.5 years, with all patients showing evidence of recurrent disease 12 .…”
Section: Discussionmentioning
confidence: 95%